Environmental management for the control of Triatoma dimidiata (Latreille, 1811), (Hemiptera: Reduviidae) in Costa Rica: a pilot project - Zeledón, Rodrigo (2006)
An ecological control method, using environmental management operations, based on biological and behavioral characteristics of Triatoma dimidiata (Latreille, 1811), was implemented as a pilot project in an area of Costa Rica where the bug is prevalent. The sample was represented by 20 houses with peridomestic colonies (two also had indoor infestation), divided in two equivalent groups of 10 each. In one group we intervened the houses, i.e. all objects or materials that were serving as artificial ecotopes for the bugs were removed, and the second group was used as control houses. After a year of periodic follow up, it became evident that in those houses with a modified environment the number of insects had decreased notoriously even after the first visits and this was more evident after a period of 12.5 to 13.5 months in which no insects were detected in eight of the houses. It also became clear that in this group of houses, recolonization by wild bugs from the surrounding areas, became more difficult, probably due to the absence of protection from bug predators. In the control houses, with the exception of three in which the inhabitants decided to intervene on their own, and another house with a peculiar situation, the insect populations remained the same or even showed a tendency to increase, as confirmed at the end of the experiment. We believe that the method is feasible, low costing and non contaminating. It could be used successfully in other places where T. dimidiata is common and also in countries where other species colonize peridomestic areas of homes. Environmental management of this kind should seek the participation of the members of the communities, in order to make it a more permanent control measure.